Business Risk in Moderating the Effect of Capital Structure on Financial Performance in Listed Companies in Indonesia: Risiko Bisnis dalam Memoderasi Pengaruh Struktur Modal terhadap Kinerja Keuangan pada Perusahaan Terdaftar di Indonesia - Putri Erika Wendari Harahap; Irdha Yusra (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine the effect of capital structure on financial performance as measured by Return on Asset (ROA) and the role of business risk as a moderating variable. Secondary data is taken from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period, with a total sample of 73 companies selected using purposive sampling technique. Data analysis was carried out using multiple linear regression and moderating regression analysis.The results showed that short-term debt has a significant positive effect on ROA, while long-term debt and total debt have a significant negative effect on ROA. In addition, business risk can moderate strengthen the relationship between short-term debt and ROA, but weaken the relationship between long-term debt and ROA. Meanwhile, business risk does not moderate the relationship between total debt and ROA.